METODE FATWA MAJELIS ULAMA INDONESIA - Suryani, Irma (JURIS (Jurnal Ilmiah Syariah), 2010)
In terms of legal perspective, the fatawa issued by Indonesian Council of Islamic Scholars/Ulama (MUI) theoretically have tried to apply the principles of al-Qur’an, Hadits, Ijma, dan Qiyas as practiced by the Sunnites. However, in the realization, they suffered from inconsistency. There are many of the fatawas refering to books of fiqh (Islamic jurisprudence). In terms of the content, such factors as social and political environments yield influence toward the formulation of the fatawa. On the other hand, such influence give lessons to those who are interested in Islamic laws that the products of thoughts in Islamic laws cannot be separated from the social and political conditions when the thoughts were formulated.